The Meaning of Information Accumulation in Digital Conversation Spaces: Study on WhatsApp Application Group Communication Medium - Abdullah Khusairi (RaSAIL Media Group, Semarang, Indonesia, 2024)
This study explores the dynamics of group communication and information in the digital conversation space, using descriptive qualitative research methods through participatory data collection and interviews with 112 netizens who are members of WhatsApp Groups. Meanwhile, the analysis of the results uses the theory of Critic Analysis Discourse (CDA) Ruth Wodak (1980). Wodak said that every discourse needs to be examined by the reproductive process, the social and historical context, and the power relations and ideologies that make up the discourse. The Media of Dependency Theory theory was supported by Melvin L. Defleur and Sandra Ball-Rokeach (1989). The results show that the dominance of active members in the digital conversation space, which takes place quickly all the time, in WhatsApp Groups (WAGs) creates a buildup of informational messages. Passive group members ignore the information. This is evidence of inhibition and delay in communication goals. Research findings show that there are more passive members than active members. The dominance of active members in the discourse in the WAG has shown the picture of the WAG of unbalanced group communication between members. There is a certain individual discourse power in each WAG.